1984
DOI: 10.1079/bjn19840116
|View full text |Cite
|
Sign up to set email alerts
|

Effect of guar gum on glucose and water absorption from isolated loops of jejunum in conscious growing pigs

Abstract: I . Four pigs initially of 30 kg live weight were surgically prepared with two re-entrant cannulas in the jejunum 1.0 m apart which allowed an isolated loop to be formed through which solutions were perfused. Wr-EDTA was used as a marker for measuring net secretion or absorption.2. A new Ringer solution was made, the ionic content of which resembled more closely that found in the jejunum of pigs given similar diets, than Krebs-Ringer solution.3. The absorption of glucose and water from Krebs-Ringer and new Rin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
72
3
2

Year Published

1988
1988
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 119 publications
(80 citation statements)
references
References 13 publications
3
72
3
2
Order By: Relevance
“…The produced volatile fatty acids during fermentation of dietary NSP, play a role to be used as an energy resource instead of blood glucose (Rerat, 1996). In the current study, high mannan level did not change blood glucose, however, some other studies reported that the high mannan level in the diets reduce the absorption of glucose (Rainbird et al, 1984;Yoon et al, 2010). The ability of glucomannan to lower blood glucose appears related to its viscous and soluble nature (Vuksan et al, 1999).…”
Section: Discussioncontrasting
confidence: 46%
See 1 more Smart Citation
“…The produced volatile fatty acids during fermentation of dietary NSP, play a role to be used as an energy resource instead of blood glucose (Rerat, 1996). In the current study, high mannan level did not change blood glucose, however, some other studies reported that the high mannan level in the diets reduce the absorption of glucose (Rainbird et al, 1984;Yoon et al, 2010). The ability of glucomannan to lower blood glucose appears related to its viscous and soluble nature (Vuksan et al, 1999).…”
Section: Discussioncontrasting
confidence: 46%
“…Dietary supplementation of β-mannanase may improve glucose absorption by hydrolyzing β-mannan, thus partly explaining the observed growth response to β-mannanase. Rainbird et al (1984) noticed that supplementing β-mannanase resulted in a decrease in glucose and water absorption in pigs. Present findings are consistent with data reported by Yoon et al (2010) and Kim et al (2013) who observed increase in blood glucose concentrations but no effects on the total cholesterol and triacylglycerides in pigs fed diets supplemented with β-mannanase.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to benefits from consuming gums later in the day there are also potential costs of consuming them earlier. As Power (1991) noted, they can delay glucose absorption in the small intestine (Blackburn and Johnson 1981;Tsai and Peng 1981;Johnson et al 1984;Rainbird et al 1984) and slow both gastric emptying and small intestinal passage (Blackburn and Johnson, 1981;Johnson et al 1984;Nash 1986;Power and Oftedal 1996).…”
Section: Patterns Of Gummivory Across the Daymentioning
confidence: 99%
“…Differences in the rate of digestion of starches in vivo were also seen by RCrat et al (1979), who found that glucose derived from wheat starch reached the hepatic portal vein of pigs more rapidly than that from barley. Under normal conditions the supply of brush-border disaccharidases for completing starch digestion appears to be sufficient: even when a large amount of guar gum was present in pigs in studies by Rainbird et al (1984) no reduction in the rate of maltose hydrolysis was seen.…”
Section: Transit Digestion and Absorption In The Small Intestinementioning
confidence: 99%
“…These results emphasize the dangers of interpreting movements of digesta as an indication of movements of nutrients. Guar gum reduced the rate of absorption of glucose from the jejunum in vitro (Johnson & Gee, 1981) and in vivo (Rainbird et al 1984); the reasons for this finding appear not to be a reduction in small intestinal contact area (Blackburn etal. 1984a), but seem to relate to reduced diffusion or convection of glucose to the epithelial cell surface (Blackburn et al 1984b).…”
Section: Transit Digestion and Absorption In The Small Intestinementioning
confidence: 99%